One‐Pot Intercalation Strategy for the Encapsulation of a CO‐Releasing Organometallic Molecule in a Layered Double Hydroxide. Issue 28 (16th July 2020) - Calhau, Isabel B.; Gomes, Ana C.; Bruno, Sofia M.; Coelho, Ana C.; Magalhães, Clara I. R.; Romão, Carlos C.; Valente, Anabela A.; Gonçalves, Isabel S.; Pillinger, Martyn
Abstract : The photoactivatable CO‐releasing molecule (photoCORM) [Mo(CO)3 (CNCH2 COOH)3 ] (ALF795) has been incorporated into a Zn, Al layered double hydroxide (LDH) host by a coprecipitation synthesis strategy. Powder X‐ray diffraction (PXRD) of the resultant material Zn, Al‐ALF795 showed that the ALF795 guest molecules assembled into a monolayer to give a basal spacing of 16.0 Å. FTIR and 13 C{ 1 H} CP MAS NMR spectroscopy confirmed that the molecular structure of the tricarbonyl complex was retained upon intercalation. Scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDS) and elemental analyses confirmed the phase‐purity of Zn, Al‐ALF795. The myoglobin assay was used to demonstrate that intercalated ALF795 retains the photoactive behavior of the free CORM, with a substantial fraction (42 %) of the high CO payload (2.46 mmol g –1 ) being released after exposure to UV light for 3 h under simulated physiological conditions. In addition, gas chromatography was used to track sequential light‐ and H2 O2 ‐triggered decarbonylation of free and intercalated ALF795. In biological buffer solution (HEPES), less than 2 % Mo leaching from Zn, Al‐ALF795 took place after 5 h, showing the strong capacity of the LDH host to retain the unaltered complex and decarbonylation fragments. Abstract : A photoactive carbon monoxide releasing material with a high CO payload has been prepared by using a layered double hydroxide as a carrier system for a molybdenum carbonyl isocyanoacetate prodrug. Myoglobin and gas chromatography assays were used to track light‐induced and H2 O2 ‐triggered loss of CO. Leaching tests in biological buffer solution show the high capacity of the inorganic host to retain the unaltered complex and decarbonylation fragments.